IMPROVING THE AERODYNAMICS OF A TRANSPORT AIRCRAFT WING USING A DELTA PLANFORM WINGTIP LEADING EDGE EXTENSION - D. Gueraiche; S. А. Popov (Научный вестник МГТУ ГА, 2018)
The article explores the possibility of improving the aerodynamic properties of a supercritical-airfoil wing, typical for a modern passenger aircraft, using delta planform passive devices of large relative areas, installed along the leading edge at the wing tip. Delta extensions of various configurations were considered to be used as wingtip devices, potentially improving or completely replacing classical R. Whitcomb winglets. As a result of two- and three-dimensional CFD simulations performed on DLR-F4 wing-body prototype, the potential advantage of these devices was confirmed, particularly when they are installed in a combination with an elliptical planform, largely swept, raked winglet in terms of reducing the induced drag and increasing the aerodynamic lift-to-drag ratio at flight angles of attack. The growth in lift-to-drag ratio applying these devices owes it solely to the drop in drag, without increasing the lift force acting on the wing. In comparison to the classical winglets that lead to a general increase in lifting and lateral forces acting on the wing structure, resulting in a weight penalty, the Wingtip Ledge Edge Triangular Extension (WLETE) yields the same L/D ratio increase, but with a much smaller increase in the wing loading. A study has been made of the characteristics of the local (modified) airfoil in the WLETE zone in a two-dimensional flow context, and a quantitative analysis has been conducted of the influence of WLETE on both the profile and induced drag components, as well as its influence on the overall lift coefficient of the wing. The resulted synthesis of the WLETE influence on the wing L/D ratio will consist of its influence on each of these components. A comparison of the efficiency of using delta extensions against classical winglets was carried out in a multidisciplinary way, where in addition to the changes in aerodynamic coefficients of lift and drag, the increments of magnitude and distribution of the loads acting on the wing console were studied along with the maximum resulted structural stress. The study of the growth of structural stress on the wing structure after installing WLETE, confirmed the results obtained from CFD simulations that these delta extensions do not increase and do not change the distribution of total forces and moments acting on the wing console.